2018
DOI: 10.1016/j.theriogenology.2017.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Estrus resynchronization in ewes with unknown pregnancy status

Abstract: Although fixed-time artificial insemination (FTAI) protocols are available for sheep, estrus resynchronization has not been previously reported. The objectives of this study were to evaluate the effect of estrus resynchronization with exogenous progestogen on endogenous progesterone levels and to compare pregnancy rates after two consecutive estrus synchronizations in ewes. In Experiment 1, ewes (n = 20) received an intravaginal device (IVD) containing 60 mg medroxyprogesterone acetate (MPA) for 10 days. At th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
1
14
0
1
Order By: Relevance
“…Miranda et al. (2018) proposed a negative effect of MAP devices on P4 production in ewes (5.8 ± 0.5 ng/ml for control group vs. 4.7 ± 0.5 ng/ml for MAP group on Day 15), although without negative effects on the final percentage of pregnant females. A later study found no effect on P4 values either on pregnancy or luteolysis in sheep species (Cosentino et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miranda et al. (2018) proposed a negative effect of MAP devices on P4 production in ewes (5.8 ± 0.5 ng/ml for control group vs. 4.7 ± 0.5 ng/ml for MAP group on Day 15), although without negative effects on the final percentage of pregnant females. A later study found no effect on P4 values either on pregnancy or luteolysis in sheep species (Cosentino et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In ewes, even though Miranda et al. (2018) demonstrated a negative effect on P4 production, Cosentino et al. (2019) did not.…”
Section: Introductionmentioning
confidence: 92%
“…The animals' cycles were synchronized and then subjected to artificial insemination using a mix of fresh semen collected from adult rams, as previously described. 19 Pregnancy was confirmed at 30 days by intravaginal/rectal ultrasonography. The animals were raised in an extensive farming system, with free access to water supplemented with mineral salts, pellet feed (1.5% of live weight), and alfalfa hay.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
“…Induction of estrus with an intravaginal progesteronereleasing device (IPRD) and GnRH can enhance pregnancy rates in adult ewes, and ewe lambs out of the breeding season [3] . Exogenous gonadotrophins, such as pregnant mare serum gonadotrophin (PMSG), are used to stimulate follicular growth, which increase the estrus response and ovulation rate [4,5] , and also lead to a tighter synchrony of ovulation in out-of-season estrus induction and cyclic ewes [6,7] .…”
Section: Introductionmentioning
confidence: 99%